Evaluating Factors for Student Success in a Flipped Classroom Approach - Moore, A. A. (EAI Endorsed Transactions on e-Learning, 2020)
This paper describes the application of flipped and blended learning techniques to a Final Year Computer Science course in a UK University. All student interactions with the course are recorded in the institution’s Virtual Learning Environment and a number of metrics of engagement are identified and assessed as potential indicators of success. A statistical analysis of these metrics revealed that although attendance remains a significant indicator of student success in this scenario, consistency of engagement is a more accurate guide. Results show that students with a longest average gap between engagements of 12 days or fewer are likely to achieve the highest grade, while measuring the number of days on which material was accessed or measuring the total time spent engaging with the material are less reliable measures.